Enzymatic coating of jute fabrics for enhancing anti-ultraviolent properties via in-situ polymerization of polyhydric phenols - Dong, Aixue (2016)
To enhance the anti-ultraviolent properties of technical jute fabrics, the enzymatic surface coating with the in-situ produced phenolic polymers of polyhydric phenols was investigated in this study. Firstly, the laccase-mediated polymerization of the five polyhydric phenols (catechol, resorcinol, hydroquinone, pyrogallol and phloroglucinol) was analyzed by FT-IR. Catechol and pyrogallol were polymerized together by laccase with ether bonds linked. On the contrary, the units of resorcinol, hydroquinone and phloroglucinol in their enzymatically formed polymers concatenated to each other by C-C bonds. Then, the coated jute fabrics were characterized in terms of X-ray photoelectron spectroscopy and scanning electron microscopy. The increasing of the C/O ratio on the jute fabric surface after the coating treatments supported the achievement of the enzymatic coating on jute fabrics via the in-situ polymerization of phenolic compounds and the grafting reaction of polyphenols with lignins on the surface. The sequence of the coating extent by using various polyhydric phenols was proved to be catechol, pyrogallol, resorcinol, phloroglucinol and hydroquinone in order from rich to poor according to the O-C-O component of cellulose in the C1s spectra of jute fabrics and the scanning electron microscopy photographs of jute surfaces. Lastly, the ultraviolent protection factor and the ultraviolent resistance of the coated jute fabrics were measured. The ultraviolent protective performance of jute fabrics after the coating treatments depended both on the coating amount and the chemical structure of the coated polymers. Among the tested polyhydric phenols, the polymerization of catechol obtained the best coating for ultraviolent protection. Different polyhydric phenols employed for the enzymatic coating showed different trends in ultraviolent protection factor of jute fabrics with the increasing of incubation time. The jute fabrics coated with in-situ-generated polycatechols or polyresorcinols had excellent ultraviolent resistances.